Pengaruh variasi campuran bahan bakar tongkol jagung dan tempurung kelapa terhadap unjuk kerja tungku biomassa - Joniarta, I.W.; Wijana, M.; Triadi, A.A. Alit; Iswara, I.B.K.T.H.; Adhi, I.G.A.K.C. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2018)
Agricultural waste such as corn cobs and coconut shell can be used as alternative energy. Biomass as an alternative energy can be used as a fuel in the furnace. Corncob has low calorific value and density, so it is necessary to examine the combination’s effect of corn cobs and coconut shell toward the performances of biomass furnace.The gasification furnace was the development of a furnace design on previous research. Diameter of combustion chamber is 25 cm, diameter of free air duct and secondary air duct is 2 cm, and primary air duct is 1 cm. Combined corncob and coconut shell in sequence are 100%: 0%, 80%: 20%, 60%: 40%, 40%: 60%, 20%: 80%, 0%: 100%. Investigated parameters showing the furnace performance were boiling time, FCR, power input, power output, power loss and efficiency are boiling time, FCR, operating time, power input, power output, power loss and efficiency. Test of operating time were conducted by burning fuel until burned out. Then boiling time test were conducted by heated 1 liters water from ambient temperature to boiling (between 95oC - 97oC) on a 24 cm diameter pan.The results showed that the largest operating time (1317.33 Seconds), smallest FCR (2.249 Kg/hour), smallest power loss (19.532 kW), and the highest efficiency (8.19%) obtained at 0% : 100% combination. The fastest boiling time (157 Seconds) and the largest power output (1.828 kW) was obtained at 40%: 60% combination. While the largest power input (29.286 kW) was obtained at 60%: 40%.